The geneticist who played hoops with my DNA and other masterminds from the frontiers of biotech - Duncan, David Ewing 1958- (Morrow, 2005)
While the future of human existence is literally being forged by today's genetic scientists and biotechnology leaders, the media, policymakers, ethicists, and fellow scientists alike have not been adequately communicating this tremendous potential. With the public only vaguely aware of what is happening, a new coterie of geniuses, tinkerers, tycoons, and genetic soothsayers are--for better or worse--about to alter life on earth forever. Now journalist David Ewing Duncan has written a narrative about science and personality, delving into stem cell research, cloning, bioengineering, extending life span, and genetics by telling the stories of the characters at the fulcrum of the science. Calling to mind age-old stories and myths--Prometheus, Faustus, Eve, and Frankenstein--Duncan asks the question: Can we trust these scientists?--From publisher description.